Influence of Service Quality, Facilities, and Location on Traditional Market Traders' Satisfaction (Case Study on Satrio Wibowo Market Traders Semarang) - Nurjanah, Arlisa Dwi; Inayah, Inayah -; Riyanto, Makmun - (Politeknik Negeri Semarang, 2024)
Customer satisfaction is a measurement of success in the service business. Customers feel satisfied when their needs surpassed their expectations. The market is a physical place where sellers and buyers make transactions, for traders who sell in this market, the variables of service quality, facilities and location are the main factors for trader satisfaction. This study aims to determine the effect of service quality, facilities, and location on the traditional market traders satisfaction at Satrio Wibowo Semarang. The population in this research is Market Traders at Pasar Satrio Wibowo Semarang. The method used in this research is descriptive quantitative, with the sampling method by a census/sampling total of 79 respondents. Data is analyzed by using multiple linear regression. The results showed that service quality partially has a insignificant positive effect on the traditional market traders satisfaction, but facilities and location have a significant positive effect on traditional market traders satisfaction. Simultaneously the service quality, facilities, and location have a significant positive effect. Based on the analysis of the coefficient of determination shows that the Adjusted R Square value is 0.75, it means that service quality, facilities, and location contribute to the traditional market traders satisfaction by 75%, while 25% is influenced by other variables not included in this study.